0926 Sleep Timing And The Prevalence Of Suicidal Ideation In A Community Sample. (12th April 2019) - Tubbs, Andrew S; Khader, Waliuddin S; Hale, Lauren; Branas, Charles; Perlis, Michael; Gehrels, Jo-Ann; Alfonso-Miller, Pamela; Grandner, Michael A
Abstract: Introduction: When adjusted for likelihood of wakefulness, completed suicides disproportionately occur during the night. Further clarification of the relationship between time awake at night and suicide is needed. Using a large community dataset, we compared sleep timing patterns relative to suicidal ideation. Methods: Data was acquired from the Sleep and Healthy Activity, Diet, Environment, and Socialization (SHADES) study, a survey of N=1007 adults. Frequency of suicidal ideation was extracted from the Patient Health Questionnaire - 9. Sleep timing was estimated from the Sleep Timing Questionnaire. To determine if suicidal ideation was higher at particular times during the day, the number of awake individuals with suicidal ideation was counted for each one-hour bin. We then compared these counts to the expected number of individuals with suicidal ideation based purely on the percentage of the sample awake at each one-hour bin. Dividing the observed count by the expected count produced a standardized prevalence ratio (SPR) of suicidal ideation, where an SPR of 1 meant that the observed count was equivalent to the expected count based on wakefulness. Clock hours were then grouped into 4 categories: Morning (06:00 to 11:59), Afternoon (12:00 to 17:59), Evening (18:00 to 23:59), and Night (00:00 to 05:59). Results: Out of 1004 subjects who provided complete data, 769 reported no suicidal ideation, 138 reported occasional suicidal ideation, and 97 reported frequent suicidal ideation. The mean SPRs for occasional suicidal ideation were: Morning=0.95; Afternoon=1.00; Evening=1.06; and Night=1.42. The mean SPRs for frequent suicidal ideation were: Morning=0.90; Afternoon=1.00; Evening=1.00; and Night=1.39. The nighttime SPR was significantly higher than morning, afternoon, or evening SPRs for both occasional (one-way ANOVA, p=0.003) and frequent suicidal ideation (one-way ANOVA. p<0.001). Conclusion: The standardized prevalence ratio of suicidal ideation is higher during the night than at any other time of day. This finding extends our previous work on completed suicides to encompass suicidal ideation. Support (If Any): The SHADES study was funded by R21ES022931 awarded to Dr. Michael Grandner.